Pre-discharge Cardiorespiratory Monitoring in Preterm Infants. the CORE Study - Cresi, Francesco; Cocchi, Enrico; Maggiora, Elena; Pirra, Alice; Logrippo, Federica; Ariotti, Maria Chiara; Peila, Chiara; Bertino, Enrico; Coscia, Alessandra (Frontiers in Pediatrics, 2020)
Objective: Ensuring cardiorespiratory (CR) stability is essential for a safe discharge. The aim of this study was to assess the impact of a new pre-discharge protocol named CORE on the risk of hospital readmission (RHR). Methods: Preterm infants admitted in our NICU between 2015-2018 were randomly assigned to CORE (exposed) or to standard (not-exposed) discharge protocol. CORE included 24hr-clinical observation, followed by 24hr-instrumental CR monitoring only for high-risk infants. RHR 12 months after discharge and length of stay represent the primary and secondary outcomes, respectively. Results: 323 preterm infants were enrolled. Exposed infants had a lower RHR (log-rank p<0.05). The difference was especially marked 3 months after discharge (9.09% vs. 21.6%; p=.004). The hospital length of stay in exposed and not-exposed infants was 39(26-58) and 43(26-68) days, respectively (p=0.16). Conclusions: The CORE protocol could help neonatologists to define the best timing for discharge reducing RHR without lengthening hospital stay.